Design And Implementation Of Embedded Active Rfid System With Strain Sensor - Omar, Muhammad Qayum (2014)
Conventionally, machine condition monitoring is applied in the industry, using the wired system for monitoring the machine condition. This method can cause expensive cable installation, difficult replacement, workspace limitation and manual data collection for maintenance. Therefore, it is appropriate to develop an active RFID system as a solution. The work presented in this thesis contributes to the research of the 2.4 GHz active RFID system with strain sensor integration in several ways such as the design and embedment of the RFID tag that consists of the strain sensor, microcontroller and RF transceiver module; the implementation of the RFID tag that transmits information data, wireless, to the RFID reader for data monitoring and storage; and the performance evaluation of the active RFID system in various aspects including calibration based on wireless and wired prototypes , operating frequency verification, periodic transmission accuracy, maximum read range measurement at indoor and outdoor environments and estimation of power consumption of the tag. It is observed that the strain data reading, through wired and wireless transmission from the proposed RFID system provide an acceptable, stable and less error strain reading values.